Ergot alkaloids in New Zealand pastures and their impact. Issue 1 (2nd January 2022) - Caradus, John R.; Card, Stuart D.; Finch, Sarah C.; Hume, David E.; Johnson, Linda J.; Mace, Wade J.; Popay, Alison J.
ABSTRACT: In identifying endophytes for use in pastures in New Zealand there have been two strategies used, either exclusion of ergopeptine and lolitrem alkaloids or, retaining some ergopeptine expression to enhance the stability of natural defences against invertebrate pests. Both have their strengths and weaknesses. It is a matter of balancing these to ensure the end-user has access to a product that satisfies their needs – a persistent pasture with low to nil animal toxicity in terms of animal production and welfare. The range and intensity of ergot alkaloids in grazed pasture on both pasture and ruminants is reviewed, with emphasis on New Zealand. Ergot alkaloids associated with pasture are produced by associations between certain Epichloë endophyte strains and temperate grasses. Ergot alkaloids have been shown to improve persistence of pasture through providing resistance/deterrence to insect pests as well as deterring grazing animals. However, ergovaline is toxic to grazing animals. Some commercially available ryegrass-endophyte associations can produce ergovaline concentrations close to those found in associations between ryegrass and the standard endophyte. It is feasible to eliminate ergot alkaloids from pasture grasses in New Zealand as endophyte strains are commercially available that do not express ergovaline and yet still provide excellent pest resistance.